Pengaruh Biaya Bahan Baku Dan Biaya Tenaga Kerja Terhadap Volume Produksi: (Studi Kasus Pada Pabrik Kusen Putra 99 Kabupaten Ciamis Periode 2018-2020) - Rafi Darojat (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to find out the simultaneous and partial influence of raw material costs and direct labor costs on production results in the Kusen Putra 99 Factory of Ciamis. The research method used is a causal relationship with the case study approach. The data used is secondary data where the data is obtained directly from the Kusen Putra 99 Factory of Ciamis with a sample of 3 years. Data analysis in this study is a double linear regression analysis, correlation coefficient analilsis and determination coefficient analysis with the help of the SPSS program version 25. Based on research it is known that the cost of raw materials and direct labor costs simultaneously have a significant effect on the production of Kusen Putra 99 Factory of Ciamis. The cost of raw materials partially affects the production of Kusen Putra 99 Factory of Ciamis. Labor costs directly affect the production of Kusen Putra 99 Factory of Ciamis.